Analysis of Straight Vegetable Oil (SVO) Spray Characteristic and Droplets Distribution By Using Nano-Spark Shadowgraph Photography Technique - Abdul Adam, Abdullah; R., Mamat; Kidoguchi, Yoshiyuki; Yatsufusa, Tomoaki (2011)
Abstract - Biofuel is an alternative fuel to reduce the dependent on fossil fuel due to the limited oil stock and increment of oil prices. Straight vegetable oil (SVO) has several superior combustion characteristics such as less hydrocarbons, carbon monoxide and particulate matter compared to diesel fuel. More advantages are high biodegradability, excellent lubricity and no sulfur content. During combustion, approximately 10wt% of its oxygen content promote more complete combustion process and effectively reduce unburned hydrocarbons (UHC), carbon monoxide (CO) as well as suspended aerosol carbon granules. However, high kinematic viscosity of SVO affects the spray characteristics thus effect the engine efficiency. In this study, the effect of kinematic viscosity of SVO on fuel injection spray characteristic are investigated using constant volume high pressure spray chamber and nano-spark shadowgraph photography technique.